Social information and selfishness - Potters, Jan; Xu, Yilong (Journal of economic behavior & organization, 2020)
When decision makers are informed about the decisions of their peers, does this make them more selfish or more generous? We study the effect of social information on selfishness (as measured by dictator game giving) in a twice-repeated setting. We vary whether or not dictators receive information about the allocation decisions of other dictators. Independently we vary whether being the dictator is determined randomly or earned. We find that dictators act more generously in the first round with than without social information in case dictator positions are randomly assigned; no such effect is found in case dictators’ positions are earned. Allocations in the second round are generally more selfish than those in the first round. This effect is significantly stronger with than without social information, indicating that being informed about the decisions of their peers makes dictators more selfish. These results indicate that transparency about allocation decisions is unlikely to make such decisions more generous.